Sustainable Event Policy Research Review In Bali: An Integrative Literature Review Framework For Environmental And Socioeconomic Integration - Leonardo Gunawan (Journal of Social Research, 2025)
Bali's heavy reliance on tourism, particularly in the events and MICE sector, has led to growing environmental degradation, water insecurity, and socio-cultural tensions. Despite policy efforts like the Bali Tourism Levy and the Regenerative Bali Program, fragmented governance and limited integration of local customs hinder sustainable outcomes. This study aims to develop an integrative policy framework for sustainable event management in Bali that harmonizes environmental conservation, socioeconomic equity, and cultural resilience. Utilizing an integrative literature review methodology grounded in the Theory, Context, and Methodology (TCM) framework, the study synthesizes peer-reviewed research from the Scopus database to examine the interactions among event policies, ecological systems, and stakeholder dynamics. Findings reveal that event policies often neglect traditional ecological knowledge and fail to equitably distribute benefits, exacerbating environmental strain and cultural erosion. However, initiatives incorporating Balinese philosophies such as Tri Hita Karana—and involving local stakeholders like subak and banjar councils—demonstrate improved environmental stewardship and economic outcomes. The proposed framework incorporates participatory governance models (e.g., Learning & Action Alliances), mandatory sustainability certifications, and community-led monitoring systems to synchronize ecological limits with social and cultural priorities. This research contributes to theory by advancing a Quadruple Bottom Line model that fuses cultural resilience into socio-ecological governance and suggests pathways for replicable, culturally embedded policy design in other tourism-dependent island settings.